2016
DOI: 10.1136/jmedgenet-2016-104178
|View full text |Cite|
|
Sign up to set email alerts
|

Oral pharmacological chaperone migalastat compared with enzyme replacement therapy in Fabry disease: 18-month results from the randomised phase III ATTRACT study

Abstract: BackgroundFabry disease is an X-linked lysosomal storage disorder caused by GLA mutations, resulting in α-galactosidase (α-Gal) deficiency and accumulation of lysosomal substrates. Migalastat, an oral pharmacological chaperone being developed as an alternative to intravenous enzyme replacement therapy (ERT), stabilises specific mutant (amenable) forms of α-Gal to facilitate normal lysosomal trafficking.MethodsThe main objective of the 18-month, randomised, active-controlled ATTRACT study was to assess the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
276
2
15

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 297 publications
(314 citation statements)
references
References 56 publications
8
276
2
15
Order By: Relevance
“…The general trend of a decline we observed in lyso‐Gb3 levels was consistent with recent findings from the migalastat phase III ATTRACT study . In our study, lyso‐Gb3 levels significantly declined, followed by stabilization, but one patient who had switched from ERT to migalastat showed a rapid increase in lyso‐Gb3 from baseline (12.4–66.1 ng/mL at the second follow‐up).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The general trend of a decline we observed in lyso‐Gb3 levels was consistent with recent findings from the migalastat phase III ATTRACT study . In our study, lyso‐Gb3 levels significantly declined, followed by stabilization, but one patient who had switched from ERT to migalastat showed a rapid increase in lyso‐Gb3 from baseline (12.4–66.1 ng/mL at the second follow‐up).…”
Section: Discussionsupporting
confidence: 91%
“…30 Mehta et al 31 observed a mean yearly decline of 2.46−3.58 mL/minute/1.73 m 2 with ERT. Compared with those findings, and other studies that described first experiences with migalastat, 11,23 we detected an overall greater reduction in renal function (−9 mL/minute/1.73 m 2 ) in the total cohort after 1 year of migalastat therapy. However, in our study seven patients displayed a baseline estimated GFR > 80 mL/minute/1.73 m 2 in which the precision of GFR values remains suboptimal.…”
Section: Renal Biomarkerssupporting
confidence: 54%
“…Eliglustat, another GCS inhibitor that does not penetrate the CNS, was also approved for Gaucher disease in 2014. Other GCS inhibitors in clinical devel opment include lucerastat, a miglustat analogue with an improved safety profile that is currently in a phase III trial for Fabry disease (FD) 236,286 , and ibiglustat, which penetrates the CNS. The latter is in clinical development for FD (phase II), for Gaucher disease type 3 (phase II) and for patients with PD who carry a mutation in GBA (phase II).…”
Section: Substrate Reduction Therapies and Small-molecule Chaperonesmentioning
confidence: 99%
“…Two recent phase III studies (the FACETS and ATTRACT studies, NCT00925301 and NCT01218659, respectively) evaluating the safety and efficacy of the chaperone drug migalastat, which targets certain GLA mutations that affect enzyme conformation, have demonstrated favourable clinical outcomes for patients carrying these mutations compared with placebo or enzyme replacement therapy 113,114 . Migalastat has since been approved for the treatment of Fabry disease by the European Medicines Agency, and a new drug application will be submitted to the FDA by the end of this year (see Further information).…”
Section: Precision Medicine and Drug Developmentmentioning
confidence: 99%